2012
DOI: 10.5539/mas.v6n8p63
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported ADHD Symptoms Prevalence in a University Student Population: Using Adult Self-Report-V1.1 Screener

Abstract: The aim of this study was to examine the prevalence of adult's attention deficit/hyperactivity symptoms among the University students in Iran. This descriptive-analytical study conducted on 403 University students of Sistan and Baluchestan in second half of the educational year of 2010-2011. For gathering the data we used Adler, Kessler-Spenser Hyperactivity Questionnaire. All participants were asked to complete the Adult Self-Report Scale-V1,1 (ASRS-VI.I). Findings: Considering the subscale of attention-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Only 3 studies reported the prevalence rates based on gender. In the studies published by Sadeghi Movahed et al ( 35 ) and Bakhshani et al ( 34 ) ADHD was more common in males than in females and in the study of Jahangard et al ( 39 ) the prevalence estimates for ADHD in adults did not differ significantly between genders.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Only 3 studies reported the prevalence rates based on gender. In the studies published by Sadeghi Movahed et al ( 35 ) and Bakhshani et al ( 34 ) ADHD was more common in males than in females and in the study of Jahangard et al ( 39 ) the prevalence estimates for ADHD in adults did not differ significantly between genders.…”
Section: Resultsmentioning
confidence: 84%
“…Data were collected using Conners' Adult ADHD Rating Scales (CAARS-S:S), Adult ADHD Self-Report Scale (ASRS-v1.1), Wender Utah Rating Scale, Wender–Reimherr structured interview, and clinical interviews based on DSM-IV and DSM-IV-TR criteria. Total prevalence of ADHD ranged between 3.9% in the study of Parvaresh et al ( 44 ) and 25.1% in that of Bakhshani et al ( 34 ). Only 3 studies reported the prevalence rates based on gender.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It first described as a childhood disorder that affects about 2-18% of school aged children ( Faraone, Sergeant, Gillberg, & Biederman, 2003 ; Polanczyk et al, 2007 ; Rowland, Lesesne, & Abramowitz, 2002 ). Although it was first believed as a child-aged disorder but evidence showed that it continue into adulthood ( Bakhshani, Babaei, & Raghibi, 2012 ; Kessler et al, 2006 ), and about 5% of adults may suffer from it ( American Psychiatric Association, 2000 ; Biederman & Faraone, 2005 ; Faraone, Biederman, & Mick, 2006 ; Kessler et al, 2006 ). ADHD characterized by inappropriate levels of inattention, hyperactivity and impulsivity ( American Psychiatric Association, 2000 ), that was initially known as hyperactive (hyperkinetic) disorder ( Curatolo, D'Agati, & Moavero, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% to 70% of children suffering from the ADHD enter adolescence with their affliction, and doctors prescribe a continuation of therapy for them (3,4). Different studies report an ADHD incidence of 0.3% to 6% in adults (1,(5)(6)(7)(8)(9). The incidence rate is also high, 30% to 50%, among drug abuse patients (10), which makes responding to therapy difficult for them (6,11).…”
Section: Introductionmentioning
confidence: 99%